Born that way: Beliefs about genetics' importance and redistribution preferences - Andrea Pogliano (Tinbergen Institute, 2024)
Meritocratic fairness justifies inequality when it stems from performance. Yet performance is influenced by one's genetics. I investigate whether individuals' redistribution preferences are affected by their beliefs about genetics' role in generating performance inequality. In an incentivized online experiment, impartial spectators can redistribute the earnings that two workers earned based on their performance in a mathematical task. Across two treatments, I modify beliefs about the importance of genetics in performing in the task by means of an information provision treatment. I find that spectators for whom genetics is framed to play a larger role compensate the worse performer more, compared to those for whom genetics is framed to play a smaller role. When comparing the spectators' decisions before and after the provision of information, I find that about 23% of spectators compensate the worse performer more whereas the majority does not change their allocation. This study highlights that individuals' redistribution preferences are affected by their beliefs about genetics' role in generating performance inequality.
Keywords: C90; C91; D63; D90; H23; 330; Meritocracy; Genetics; Beliefs; Fairness; Inequality